2017
DOI: 10.3389/fmicb.2017.00616
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Disease Spectrum Linked to a Novel IL-12Rβ1 N-Terminal Signal Peptide Stop-Gain Homozygous Mutation with Paradoxical Receptor Cell-Surface Expression

Abstract: Patients with Mendelian Susceptibility to Mycobacterial Diseases (MSMD) exhibit variable vulnerability to infections by mycobacteria and other intramacrophagic bacteria (e.g., Salmonella and Klebsiella) and fungi (e.g., Histoplasma, Candida, Paracoccidioides, Coccidioides, and Cryptococcus). The hallmark of MSMD is the inherited impaired production of interferon gamma (IFN-γ) or the lack of response to it. Mutations in the interleukin (IL)-12 receptor subunit beta 1 (IL12RB1) gene accounts for 38% of cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Two of the patients (P2 and P3) also presented recurrent invasive salmonellosis and a third (P1) had gastroenteritis caused by Salmonella . In P2, salmonellosis was associated with leukocytoclastic vasculitis (Figure 1B), a feature previously reported in eight other patients with IL-12Rβ1 deficiency and Salmonella infections [3, 4, 9, 14, 18, 22, 4749]. Three patients (P1, P2, and P6) experienced fungal disease, mostly mucocutaneous infection with Candida spp.…”
Section: Resultssupporting
confidence: 63%
“…Two of the patients (P2 and P3) also presented recurrent invasive salmonellosis and a third (P1) had gastroenteritis caused by Salmonella . In P2, salmonellosis was associated with leukocytoclastic vasculitis (Figure 1B), a feature previously reported in eight other patients with IL-12Rβ1 deficiency and Salmonella infections [3, 4, 9, 14, 18, 22, 4749]. Three patients (P1, P2, and P6) experienced fungal disease, mostly mucocutaneous infection with Candida spp.…”
Section: Resultssupporting
confidence: 63%
“…Since the discovery of its first genetic etiology in 1996, MSMD has been reported and a causal genetic lesion described in 501 individuals from 356 kindreds originating from 57 countries on five continents (Figure a). Over this period, the genetic dissection of MSMD in these patients has revealed this condition to be caused by inborn errors of interferon (IFN)‐γ immunity . These findings confirm that IFN‐γ, first described in 1965 as an antiviral IFN, is actually the macrophage‐activating factor, as shown in 1983 .…”
Section: Introductionsupporting
confidence: 61%
“…Since the last comprehensive review on MSMD in 2014, three new genetic disorders have been reported, caused by mutations of TYK2 and SPPL2A, (two novel genetic etiologies) and IFNGR2 (a novel allelic form). Moreover, new mutations associated with the other 18 disorders have also been reported . We also discuss here two recently reported syndromic forms of MSMD: AR RORγ/RORγT and Janus kinase (JAK)1 deficiencies .…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations